2019
DOI: 10.3390/brainsci9100267
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange in Multiple Sclerosis and Autoimmune Encephalitis: A Comparative Study of Indication, Efficacy, and Safety

Abstract: Therapeutic plasma exchange (TPE) is a well-established method of treatment for steroid-refractory relapses in multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD). Little is known about indications and clinical responses to TPE in autoimmune encephalitis and other immune-mediated disorders of the central nervous system (CNS). We performed a retrospective chart review of patients with immune-mediated disorders of the CNS undergoing TPE at our tertiary care center between 2003 and 2015. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…Generally, the number of treatment cycles was approximately five, consistent with descriptions that report a total fluid exchange divided five times in MG [24], GBS [22], and CIDP [3,25]. Jiao et al reported a slightly different range, 2-7 treatment cycles, in 29 patients with NMOSD [26], and Moser et al reported a wider range of cycles, 3-13, in 12 patients with AE [27].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Generally, the number of treatment cycles was approximately five, consistent with descriptions that report a total fluid exchange divided five times in MG [24], GBS [22], and CIDP [3,25]. Jiao et al reported a slightly different range, 2-7 treatment cycles, in 29 patients with NMOSD [26], and Moser et al reported a wider range of cycles, 3-13, in 12 patients with AE [27].…”
Section: Discussionsupporting
confidence: 74%
“…In the analyses of the complications, hypotension occurred in approximately half of our patients even though a replacement solution was provided with TPE to prevent this outcome; this differs to apheresis where there is no fluid replacement [ 2 ]. Nonetheless, hypotension is common when using TPE for different indications [ 27 31 ]. Hydroelectrolytic disorders were the second-most frequent adverse reaction, not only in our study but also in the study by Clarck et al, who found that 59 of their patients required the replacement of at least one electrolyte after TPE (primarily for potassium and magnesium abnormalities) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, the percentage of patients experiencing improvements after PLEX was 83% among those with neuronal cell surface antibodies and 66.7 % among those with antibodies against intracellular-synaptic sites, while none of the patients with intracellular antigens experienced improvements after PLEX (Heine et al 2016 ). A recent retrospective study found that 75% of patients with AE respond to PLEX, which also had a favourable safety profile (Moser et al 2019 ). Several other studies have also confirmed the efficacy of PLEX in AE (Fassbender et al 2017 ).…”
Section: Autoimmune Encephalitismentioning
confidence: 99%
“…Side-effects include disturbances of coagulation, vasovagal episodes, fluid overload or under-replacement, allergic or anaphylactic reactions due to plasma infusion, and catheter-associated infections [33]. The average number of PLEX cycles in patients with autoimmune encephalitis was 6.3 [34], which is in line with the five cycles in a retrospective multicentre study of MOG-ab-positive patients with TM and/or ON [22]. In adults with MOGAD, 3e5 cycles of PLEX are recommended [35].…”
Section: Plasma Exchange (Plex)mentioning
confidence: 99%